The Effect of Teacher Competence, Learning Facilities, and Learning Readiness on Students' Learning Achievement Through Learning Motivation of Grade 11 Accounting Lesson in Brebes Regensy Vocational High School - Alif, M. Hessal; Pujiati, Amin; Yulianto, Arief (Universitas Negeri Semarang, 2020)
The purpose of this study was to determine a) the effect of teacher competence on learning motivation; b) the effect of learning facilities on learning motivation; c) the effect of learning readiness on learning motivation; d) the effect of learning motivation on learning achievement. The results of this study are a) teacher competence effects learning motivation. b) learning facilities affects learning motivation c) readiness affects learning motivation. d) learning motivation affects learning achievement. As many as 171 students were taken as sample by using Purposive Sampling. Sampling this using the formula slovkin. The results of the study showed that the competence of teachers affect the motivation to learn. Learning facilities affect the learning motivation. Learning readiness influences motivation to learn, and motivation to learn affect learning achievement.